Molecular Surveillance of Pyrethroid Resistance of Dengue Vector [Aedesaegypti] and its Implication To Public Health - Sayono -; Ulfa Nurullita; Irfanul Chakim (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2016)
Abstract.Resistance of Aedesaegypti mosquito to pyrehtoid compounds have been a common problem in controlling thisdisease among the tropical countries, including Indonesia. Knockdown resistance alleles of voltage-gated sodium channel gene have been proposed as an effective marker for early detection of this problem. This study aimed to understand the pyrethroid resistance status of Aedesaegypti population among Dengue endemic areas in Central Java Province. The house hold larval surveys were conducted in Temanggung, Kendal and Jepara districts and Semarang municipal based on the Dengue cases. Mosquito larvae were reared to be 3-5 days old imago stage in entomologic laboratory, and then subjected to molecular experiment for detection of kdr alleles of domain II VGSC gene. This study found two single nucleotide polymorphisms, namely S989P and V1016G. These SNPs indicated that Aedesaegypti population has developed resistant to pyrethroid compounds. Generally, we found the high percentage of those SNPs, namely 26 and 93 percents. It is an important data input for public health officer in planning of Dengue prevention.